Motivation at work of brazilian executives - Chavaglia, J. N.; Filipe, J. A.; Ferreira, M. A. M.; Calliari Jr, I. (International Journal of Latest Trends in Finance and Economics Sciences, 2014)
This study aimed to verify the extent to which the Brazilian executives are motivated at work. Companies seek constantly for practices that allow greater motivation of employees in day-to-day activities. Such search gets particularly important when looking at the work of executives in Brazil, in which working conditions are extremely stressful, whether by race against time, either by issues relating to the relationship among people. Traditional management theory seems to be ineffective when searching for the solution of problems related to the process of management of employees motivation.